Refugee Economies in Addis Ababa: Towards Sustainable Opportunities for Urban Communities? - Betts, A; Fryszer, L; Omata, N; Sterck, O (Refugee Studies Centre, 2019)
Addis Ababa has only 22,000 registered refugees, out of a national refugee population of 900,000. They comprise two main groups: 17,000 Eritreans who are there on the socalled Out-of-Camp Policy (OCP) based on their capacity to be self-reliant, and 5,000 Somali refugees who are mainly there on the Urban Assistance Programme (UAP) because of specific vulnerabilities that cannot be met in camps. The UAP refugees receive financial assistance; the OCP refugees do not. Based on qualitative research and a survey of 2,441 refugees and members of the proximate host community, we examine the economic lives of the refugee communities and their interactions with the host community. In this report, we draw upon the data to consider the prospects for a sustainable urban response in the context of Ethiopia’s adoption of the new Refugee Proclamation in 2019, which appears to provide refugees with the right to work and freedom of movement.